2003
DOI: 10.1088/0954-3899/29/5/313
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the electric field of the atmosphere on cosmic rays

Abstract: A review of the present-day situation in the experimental studies of variations of cosmic rays during thunderstorms is given. It is shown that these experiments can be a useful tool for studying very interesting physical effects in the electrically disturbed atmosphere. The main emphasis is laid on the experimental verification of the runaway breakdown theory and on the role of cosmic rays in the processes of lightning initiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Finally, direct observations of cosmic-ray secondary muons show that thunderstorm electric fields can either increase or decrease their flux slightly, depending on the sign of the field and the relative population of positive and negative muons (Alexeenko et al 2002;Lidvansky 2003;Muraki et al 2004). …”
Section: Glows Observed From the Groundmentioning
confidence: 99%
“…Finally, direct observations of cosmic-ray secondary muons show that thunderstorm electric fields can either increase or decrease their flux slightly, depending on the sign of the field and the relative population of positive and negative muons (Alexeenko et al 2002;Lidvansky 2003;Muraki et al 2004). …”
Section: Glows Observed From the Groundmentioning
confidence: 99%
“…secondary particles generated from the solar protons. Other sources of high-energy particles in the lower atmosphere include thunderstorms (Wilson 1925;Lidvansky 2003), from which there is surface experimental evidence for accelerated electrons (Khaerdinov et al 2005).…”
Section: K2mentioning
confidence: 99%
“…As far as the amplitudes of observed effects are concerned, it is even rather modest. Here, the maximum enhancement of the soft component hardly exceeds 5% (at the best time resolution), while in the events published earlier the maximum enhancements are bigger than 20% (September 7, 2000 [1,2]) and 30% (October 11,…”
Section: Methodsmentioning
confidence: 59%
“…When studying the intensity variations of secondary cosmic rays during thunderstorms [1] with the Carpet shower array of the Baksan Neutrino Observatory it was found that, in addition to regular variations correlating with the near-ground electric field, there existed considerable transient changes of the intensity [2,3].…”
Section: Introductionmentioning
confidence: 99%